Antineoplastic effect of pectic polysaccharides from green sweet pepper (Capsicum annuum) on mammary tumor cells in vivo and in vitro. (1st December 2018) - Adami, Eliana Rezende; Corso, Claudia Rita; Turin-Oliveira, Natalia Mulinari; Galindo, Claudia Martins; Milani, Letícia; Stipp, Maria Caroline; do Nascimento, Georgia Erdmann; Chequin, Andressa; da Silva, Luisa Mota; de Andrade, Sérgio Faloni; Dittrich, Rosangela Locatelli; Queiroz-Telles, José Ederaldo; et al.
Graphical abstract: Highlights: The polysaccharides from green sweet pepper (CAP) presented antineoplastic effects against mammary tumor lineages. CAP treatment reduced the gene expression of VEGF in tumor cells in vivo and in vitro . CAP treatment reduced the area of vessels in Ehrlich tumor. CAP treatment induced necrosis in Ehrlich solid tumors. CAP treatment increased the levels of IL-6 in Ehrlich tumors in mice. Abstract: The present study investigated the antineoplastic effects of pectic polysaccharides that were extracted from green sweet pepper ( Capsicum annuum [CAP]) in the Ehrlich carcinoma in mice and in human mammary tumor lineages. After the subcutaneous inoculation of 2 × 10 6 Ehrlich tumor cells, Female Swiss mice received 50, 100, or 150 mg/kg CAP or vehicle orally once daily or methotrexate (2.5 mg/kg, i.p., every 5 days) for 21 days. CAP dose-dependently reduced Ehrlich tumor growth. It also reduced the viability of MCF-7, MDA-MB-231, and MDA-MB-436 human mammary cell lineages. Treatment with CAP reduced the gene expression of vascular endothelial growth factor in vivo and in vitro, reduced vessel areas of the tumors, and induced necrosis in Ehrlich solid tumors. CAP treatment significantly increased Interleukin-6 in tumors. The antineoplastic effect of CAP appears to depend on the regulation of inflammation and angiogenesis. Further studies are encouraged to better understand the CAP potential for the treatment of breast tumors.